A Conflict or War Impediment Strategic Approach: Perception Games, Deception Hypergames, and Deterrence in Global Politics (Global Journal of Human-Social Science, 2022)
This article enhances the use of the applied game theory and hypergame theory in global politics and strategic security studies It suggests first a Deception Hypergame Model of Inter-state Conflict where conditions of certainty and uncertainty perception and deception are considered within a conflict war impediment perspective
Keywords: game theory; hypergame theory; strategy; equilibrium; deterrence; conflict; war